2007
DOI: 10.1042/bj20070294
|View full text |Cite
|
Sign up to set email alerts
|

Differential membrane binding and diacylglycerol recognition by C1 domains of RasGRPs

Abstract: RasGRPs (guanine-nucleotide-releasing proteins) are exchange factors for membrane-bound GTPases. All RasGRP family members contain C1 domains which, in other proteins, bind DAG (diacylglycerol) and thus mediate the proximal signal-transduction events induced by this lipid second messenger. The presence of C1 domains suggests that all RasGRPs could be regulated by membrane translocation driven by C1-DAG interactions. This has been demonstrated for RasGRP1 and RasGRP3, but has not been tested directly for RasGRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(68 citation statements)
references
References 74 publications
4
64
0
Order By: Relevance
“…Previous studies in cell lines demonstrated that the C1 domain in CalDAG-GEFI is atypical and thus binds DAG with very low affinity. 16,41,42 C1 domains, however, are also known as protein interaction modules. 43 Their binding partners include adapter proteins such as 14-3-3 44 and Ras guanosine triphosphtases, 45 both of which are important in integrin inside-out activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in cell lines demonstrated that the C1 domain in CalDAG-GEFI is atypical and thus binds DAG with very low affinity. 16,41,42 C1 domains, however, are also known as protein interaction modules. 43 Their binding partners include adapter proteins such as 14-3-3 44 and Ras guanosine triphosphtases, 45 both of which are important in integrin inside-out activation.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] In addition to the GEF domain, CalDAG-GEFI contains a pair of Ca 2ϩ binding EF hand domains and a C1-like domain with hitherto unknown function. 16 DAG is a well-established activator of protein kinase C (PKC) and therefore granule release in platelets. 17,18 PKC-dependent integrin activation depends on positive feedback by the Gi-coupled P2Y12 receptor, 19 which again leads to the activation of Rap1.…”
Section: Introductionmentioning
confidence: 99%
“…coli Expression and Purification of Selenomethionine-incorporated CCT236-The cDNA encoding CCT236 was transferred from the baculovirus shuttle vector into pGEX6p1 via NcoI and BamHI cloning sites, to create a fusion protein with a PreScission protease-cleavable glutathione S-transferase tag. The pGEX6p1-CCT236 plasmid was transformed into the BL21-derived Rosetta cell strain (Novagen) for protein expression (18). The overexpression protocol for selenomethionineincorporated protein was based on the method of Doublié (19).…”
Section: Methodsmentioning
confidence: 99%
“…The H168A,Y173A double mutant was created by introducing the Y173A mutation into the H168A template plasmid, using QuickChange and the same mutagenic primer detailed above. The GST-CCT mutant proteins were expressed in BL21 Rosetta cells (18), purified via glutathione affinity chromatography, and cleaved with PreScission protease, as described above. The protein concentrations in the pooled elution fractions were measured by the Bradford assay (37).…”
Section: Methodsmentioning
confidence: 99%
“…1,2 Because RasGRP2 cannot bind DAG, it fails to translocate to membranes in vivo in response to DAG analogs. 3 RasGRP2, also called CalDAG-GEFI, plays a role in controlling T-cell and platelet adhesion through Rap1 activation, 4,5 and is involved in integrin-independent neutrophil chemotaxis. 6 RasGRP2 has been reported to be associated with Huntington disease and immune-mediated thrombocytopenia and thrombosis.…”
Section: Introductionmentioning
confidence: 99%